Impaired Insulin Signaling Molecules in Triceps Muscle of Diethyl Hexyl Phthalate Treated Rat is Amelioreted by Antioxidant Vitamins - Balasubramanian, Karundevi (International Journal of Pharmaceutical & Biological Archive, 2017)
Available toxicological testing in animals and in vitro test, supported by limited human data, provideevidence linking Diethyl hexyl phthalate (DEHP) and its metabolites to a wide range of adverse effects inthe reproductive tracts, liver, skeletal muscle, lungs, kidney and fetus. Recently there has been growingconcern for the impact of plastic; polyvinylchloride (PVC) based endocrine disruptors like DEHP affectsthe function of endocrines and other organs in human beings and animals. Previous studies have shownthat exposure to DEHP results in elevated level of blood glucose, decrease in serum insulin andtestosterone level. However, specific effects of DEHP on insulin signaling molecules in triceps muscle;an organ involved in the regulation of glucose homeostasis has received only little attention. Healthyadult male albino rats of Wistar strain (Rattus norvegicus) were divided into four groups: Group I:Control; Groups II and III: DEHP treated (dissolved in olive oil at a dose of 10 and 100 mg/kg bodyweight, respectively, once daily through oral intubation for 30 days); and Group IV: DEHP (100 mg/kgbody weight) plus vitamins E (50 mg/kg body weight) and C (100 mg/kg body weight) dissolved in oliveoil and distilled water, respectively, once daily through oral intubation for 30 days. After the completionof treatments, animals were euthanized and perfused (whole body); triceps was dissected out andsubjected to assessment of various parameters. Our results demonstrate that DEHP treatment inducesROS and lipid peroxidation. Furthermore, DEHP treatment significantly decreased the levels of insulinreceptor, membrane GLUT4 protein as well as it reduces glucose uptake, oxidation and glycogen inskeletal muscle due to decreased serum insulin level. Antioxidant vitamins (C & E) have significantprotective role against the adverse effect of DEHP on these tissues of adult male albino rat. All together,these results suggest that DEHP exposure induces lipid peroxidation which disrupts the membraneintegrity and thus the insulin receptor and membrane GLUT4 proteins leading to reduced glucoseoxidation in triceps muscle. Supplementation of vitamins (C & E) prevented the DEHP-induced changes.